2016
DOI: 10.3390/horticulturae2040013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficiency of Wicking Bed Irrigation Systems for Small-Scale Urban Agriculture

Abstract: A wicking bed (WB) is a plant driven system where plants receive water through capillary rise from a self-contained coarse material-filled subsoil reservoir. WBs have been widely promoted as a water-efficient irrigation solution for small-scale and urban food gardens. However, little published research exists to support popular claims about their effectiveness. In this study, the performance of WBs was compared with best-practice, precision surface irrigation in terms of water use efficiency (WUE), fruit yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Whereas the most dominant two frequencies were daily and then weekly for bed-mixed (46%; 31%) and for raised-mixed (50%; 40%). This finding supports the only other published scientific research on wicking beds, by Semananda et al [38], who found wicking beds to be significantly more labour efficient than precision surface irrigation. While growing seedlings, their experimental wicking beds could go up to 4 weeks without irrigation, and with mature tomato plants could go 1-2 weeks without irrigation [38].…”
Section: Plos Onesupporting
confidence: 90%
“…Whereas the most dominant two frequencies were daily and then weekly for bed-mixed (46%; 31%) and for raised-mixed (50%; 40%). This finding supports the only other published scientific research on wicking beds, by Semananda et al [38], who found wicking beds to be significantly more labour efficient than precision surface irrigation. While growing seedlings, their experimental wicking beds could go up to 4 weeks without irrigation, and with mature tomato plants could go 1-2 weeks without irrigation [38].…”
Section: Plos Onesupporting
confidence: 90%
“…In the first fertilizer application time (30 DAT), the control treatment received 1.95 mL fertilizer per plant, whereas treatments maintaining SMC at 80%, 70% and 60% FC received 1.66 mL, 1.46 mL and 1.28 mL per plant, respectively. All side shoots were pruned to maintain the plant in one stem, which is a standard practice [47,48].…”
Section: Crop Development Monitoringmentioning
confidence: 99%
“…Contact between water surface and growing substrate ensures water availability within the rhizosphere due to upward water movement associated with hydrophilic nature of the growing substrate. This system is using similar principle to wicking hydroponic system (Datta, 2015;Semananda et al, 2016). Garcia and Mendoza (2008) reported that high soil or substrate water content increased shoot growth, but excessive water condition could limit root growth.…”
Section: Vertical and Horizontal Shoot Growthmentioning
confidence: 99%